Ethics in Advertisements and its Impact - Dhanabhakyam, M.; Geetha, S. (Indian Journal of Marketing, 2006)
The field of advertising is extremely broad and diverse. In general terms the course of advertisement is simply a public notice meant to convey information and invite patronage or some other response. It suggests that, advertising has two basic purposes: to inform and to persuade. While these purposes are distinguishable very often both are simultaneously present. Advertising is not the same as marketing (the complex of commercial involved in transferring goods from producers and consumers) or public relations (the systematic effort to create a favorable public impression or 'image' of some person, group or entity). In many cases, though it is a technique or an instrument employed by one or both of these.